2011
DOI: 10.1007/s11258-011-9957-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the expression of direct and indirect defence traits of young plants of Mallotus japonicus in relation to soil nutritional conditions

Abstract: Although soil nutrients can influence the defence strategy of plants that have multiple defence traits, to date, there have been few studies to examine this. To evaluate the effect of soil nutrients on multiple plant defences, we cultivated Mallotus japonicus under three soil nutritional conditions in the field, and experimentally examined the expression of a physical defence trait (trichomes), chemical traits (pellucid dots), and biotic traits (extrafloral nectaries (EFNs) and pearl bodies) of the plants, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…and Macaranga triloba, the productivity of food bodies depends on the amount of available soil nutrients (Folgarait & Davidson 1995;Heil et al 2002). Yamawo & Hada (2010), Yamawo, Hada & Suzuki (2012) and Yamawo et al (2012a) reported that food bodies of M. japonicus increased under low light conditions or under high soil water/nutrient conditions. At treefall gaps, light availability is low and soil water contents are high.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…and Macaranga triloba, the productivity of food bodies depends on the amount of available soil nutrients (Folgarait & Davidson 1995;Heil et al 2002). Yamawo & Hada (2010), Yamawo, Hada & Suzuki (2012) and Yamawo et al (2012a) reported that food bodies of M. japonicus increased under low light conditions or under high soil water/nutrient conditions. At treefall gaps, light availability is low and soil water contents are high.…”
Section: Discussionmentioning
confidence: 99%
“…Yamawo & Hada (2010) reported that the increase in EFN size and the decrease in food bodies occurred under high light conditions in young M. japonicus plants. Moreover, Yamawo, Hada & Suzuki (2012) and Yamawo et al (2012a) demonstrated that, in high soil nutrient and high moisture conditions, young M. japonicus increased EFNs and EF-nectar volume and decreased the densities of trichomes and pellucid dots. However, the effects of these resistance traits on herbivory and the plant tolerance to herbivory under different abiotic conditions have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…We used seedlings of M. japonicus , a pioneer plant that grows in gaps and disturbed areas in temperate and subtropical regions of eastern Asia. The plant bears EFNs on its leaf edges (Yamawo, Katayama, Suzuki, & Hada, ), which secrete nectar that contains primary sugars used in the production of leaves (Yamawo et al., ). Instead, of the physical and chemical defenses provided by trichomes and pellucid dots, which function on young leaves, the EFNs mostly function on middle‐aged leaves and attract ants, thereby reducing leaf damage by eliminating herbivores from the plant (Yamawo, Tagawa, Hada, & Suzuki, ; Yamawo, Suzuki, et al., ).…”
Section: Methodsmentioning
confidence: 99%